PEACE ACTS AS AN ALTERNATIVE FOR SHARIA FINANCING DISPUTE SETTLEMENT: A CASE STUDY OF THE MAGETAN RELIGIOUS COURT DECISION No. 57/Pdt.GS/2025/PA.Mgt - fadlila, annisa zakiyatul; Rohmawati, Rohmawati; dwiyanti, erma (Universitas Muhammadiyah Surabaya, 2025)
Borrowing money through Islamic financial institutions has become a necessity for society. However, Islamic financing practices are still exposed to credit risks such as arrears and bad debts. Such cases require effective solutions that protect both the bank and the customer. One practical and legally binding option is a court-approved settlement agreement. The choice of a settlement agreement in this study is based on the consideration that litigation is often time-consuming, costly, and causes tension between parties. In contrast, a settlement agreement offers a faster, more efficient process while providing legal certainty equivalent to a court ruling. It also reflects the Islamic principle of ishlah (peace), which upholds deliberation and justice without neglecting legal certainty. This study aims to analyze the role of settlement agreements in resolving problematic Islamic financing disputes, with a case study of the Magetan Religious Court Decision No. 57/Pdt.GS/2025/PA.Mgt. The research uses a normative juridical method with a case approach through literature review, decision documentation, and references to procedural civil and Islamic economic law. The results show that the dispute between PT. BPRS (Perseroda) and the customer were resolved through a peace agreement involving payment of arrears and one-year financing restructuring, confirmed by the judge as a valid settlement. The study concludes that a settlement agreement is an effective, quick, and just dispute resolution instrument aligned with the principles of deliberation and justice in Islamic law.